ANALYSIS OF LYCOPENE CONTENT IN RED GUAVA JUICE (PSIDIUM GUAJAVA L.) BY VISIBLE SPECTROPHOTOMETRY - Hastuti, Aprilia Asri Hastuti Asri; Dhurhania, Crescentiana Emy (Universitas Muhammadiyah Magelang, 2024)
Red guava (Psidium guajava L.) is a fruit that is rich in phytochemicals that are beneficial for health and is widely consumed in the form of juice. Lycopene belongs to the carotenoid group which has antioxidant potential and has an important role in the immune system to deal with homeostatic changes caused by oxidative stress. Lycopene is contained in a lot of red fruit. The purpose of this study was to analyze the lycopene content in red guava juice by visible spectrophotometry. Red guava juice extracted using n-hexane:acetone:methanol 1:2:1. Qualitative analysis was carried out by observing the spectrum, then measuring the maximum wavelength, which was supported by observing the spots by thin layer chromatography on silica gel 60 GF254 plate using petroleum ether:acetone 9:1. Quantitative analysis was carried out by measuring absorbance by visible spectrophotometry at 470 nm. The results of qualitative analysis by visible spectrophotometry obtained 3 typical peaks of the lycopene spectrum at 400-550 nm, with a typical maximum wavelength of lycopene at 470 nm. Qualitative analysis by thin layer chromatography obtained spot with Rf 0.64. The results of quantitative analysis obtained lycopene levels of 2.91 ± 0.465 mg/100 grams of juice.